Stigmatization and quality of life – psychological impact of congenital melanocytic naevi. (22nd May 2020) - Szalai, Z.Z.
Abstract : Linked article: K. Neuhaus, et al. J Eur Acad Dermatol Venereol 2020; 34: 1105–1111. https://doi.org/10.1111/jdv.16131 .